Focal adhesion kinase regulates the activity of the osmosensitive transcription factor TonEBP/NFAT5 under hypertonic conditions - Neuhofer, Wolfgang (Frontiers in Physiology, 2014)
TonEBP/NFAT5 is a major regulator of the urinary concentrating process and is essential for the osmoadaptation of renal medullary cells. Focal adhesion kinase (FAK) is a mechanosensitive non-receptor protein tyrosine kinase expressed abundantly in the renal medulla. Since osmotic stress causes cell shrinkage, the present study investigated the contribution of FAK on TonEBP/NFAT5 activation. Osmotic stress induced time-dependent activation of FAK as evidenced by phosphorylation at Tyr-397, and furosemide reduces FAK Tyr-397 phosphorylation in the rat renal medulla. Both pharmacological inhibition of FAK and siRNA-mediated knockdown of FAK drastically reduced TonEBP/NFAT5 transcriptional activity and target gene expression in HEK293 cells. This effect was not mediated by impaired nuclear translocation or by reduced transactivating activity of TonEBP/NFAT5. However, TonEBP/NFAT5 abundance under hypertonic conditions was diminished by 50% by FAK inhibition or siRNA knockdown of FAK. FAK inhibition only marginally reduced transcription of the TonEBP/NFAT5 gene. Rather, TonEBP/NFAT5 mRNA stability was diminished significantly by FAK inhibition, which correlated with reduced reporter activity of the TonEBP/NFAT5 mRNA 3′ untranslated region (3′-UTR). In conclusion, FAK is a major regulator of TonEBP/NFAT5 activity by increasing its abundance via stabilization of the mRNA. This in turn, depends on the presence of the TonEBP/NFAT5 3′-UTR.